Opening the Black Box of CSR Decision Making: A Policy-Capturing Study of Charitable Donation Decisions in China - Wang, Shuo; Gao, Yuhui; Hodgkinson, Gerard P.; Rousseau, Denise M.; Flood, Patrick C. (Journal of business ethics, 2015)
This policy-capturing study, conducted in China, investigated the cognitive basis of managerial decisions to make a corporate charitable donation, a global issue in the context of corporate social responsibility (CSR) research and practice. Participants (N = 376) responded to a series of scenarios manipulating pressure from the five stakeholders (government, customers, competitors, employees, and shareholders) most commonly addressed by CSR research. The independent variables examined included organizational factors (industry, ownership, previous company donation, firm size, firm age, and perceived CEO attitudes toward charity) and the participants' personal values. Results indicate a large positive effect of shareholder and governmental pressure on the decision with lesser positive effects from customers and competitors. Surprisingly, employee pressure had a negative effect on the decision to make a charitable donation. Further, personal values and perceived CEO attitudes toward charity were significantly related to the decisions participants made. In line with our theorizing, the findings indicate that a combination of personal, organizational, and institutional factors was salient in the minds of decision makers.